O Ensino de Ciências e o novo Ensino Médio : apreciação a partir das Escolas SESI - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
As a result of the restructuring in the educational teaching process of Brazilian schools, the update of the “Base Nacional Comum Curricular” (BNCC) becomes a requirement for all high schools beginning in 2022, leading to changes in the guidelines and guidance for science teaching. The schools linked to the “Serviço Social da Indústria” (SESI) anticipated the implementation of the Base and modified their teaching-learning methods in Natural Sciences, starting to use methodologies that emphasize the subject as the main object in the construction of their own knowledge. However, it is necessary to analyze how these institutions are developing their classes in Natural Sciences, along Novo Ensino Médio guidelines. From the documental analysis of the planning strategies and, appreciation of the teaching methods, it was verified how the methodologies could grant a feasible teaching-learning process of Natural Sciences viable and how its pedagogical structuring occurs. With this, it was noticed that the classes of Natural Sciences developed and applied according to the norms of the SESI Schools, follow the guidelines of the new BNCC; however, they are generalized and simplified, in line with the industry-oriented education model. It is important to emphasize the importance of considering this experience of implementing the New High School in these institutions, since other schools are still in the initial phase or are adapting to the BNCC and, therefore, still do not have adequate teaching material for Natural Sciences. Additionally, as a result of this analysis, an educational product linked to this dissertation was prepared, with suggestions for classes and experiments in the field of Natural Sciences, to assist those institutions and/or teachers who are in the process/transition of implementing the BNCC.
Science Teaching and the new High School Education : aassessment from the SESI Schools
Keywords: Ensino-aprendizagem; Ensino de Ciências; Ensino Médio; Base Nacional Comum Curricular (BNCC); Serviço Social da Indústria (SESI); Teaching-learning; Science teaching; New High School; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::ENSINO-APRENDIZAGEM